RISC maker. - Perry, T.S.
This article briefly describes the career of John Hennessy, who, as a computer architect, pioneered reduced-instruction-set computing (RISC). He helped evangelize RISC, in the early 1980s when most people didn't believe computers with such an architecture would ever be much use, and he started a company that proved them wrong. He led the development of a new way of organizing cache memory in multiprocessors that in the late 1980s experts said was unworkable, but is today in wide use. His role as president of Stanford University is also described. As president, Hennessy runs the university with an engineering perspective, assuming he can analyze every problem and find the best solution.
Keywords: John Hennessy; RISC; Stanford University president; Cache memory; Multiprocessors; Reduced-instruction-set computing